Диагностический классификатор на основе искусственной нейронной сети и математического моделирования - Мустецов, Н. П.; Соловьева, О. И. (ХНУРЭ, 2008)
Two techniques Neural Networks of early diagnostics most frequently meets second type sugar diabetes are considered? directly on the clinical data and with preliminary modelling recalculation.
Keywords: диагностический классификатор